PENDIDIKAN ISLAM BERBASIS LIVING QUR’AN PADA MASYARAKAT ADAT KOTA MASOHI - M. Chusnus Salim Ramadhani; Muhammad Arif Syihabuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the potential for social segregation due to differences in Islamic mass organization (Ormas) affiliations in Indonesia, which often trigger differences in religious practices. In Masohi City, this phenomenon is bridged through the "Baca Doa" tradition, a practice of Living Qur’an that unites various Islamic organizations (NU, Muhammadiyah, LDII, and Jamaah Tabligh) in one gathering. The main problem in this study is how the process of informal Islamic education and the internalization of moderation values take place amidst the diversity of these organizations through the mediation of local customs. The purpose of this study is to analyze the process of Islamic education within the "Baca Doa" tradition, identify the values of moderation (wasathiyyah) being instilled, and map the supporting and inhibiting factors in the context of the indigenous community of Masohi City. The methodology used is a qualitative approach with a descriptive ethnographic type. Data were collected through participant observation, in-depth interviews with customary and religious leaders, and documentation studies, which were then analyzed using James Spradley's Developmental Research Sequence (DRS) model. The results show that the "Baca Doa" tradition functions as an effective medium for informal Islamic education through the processes of Tarbiyah and Ta’dib. Moderation values such as Tasamuh (tolerance), Ukhuwah (brotherhood), and egalitarianism (through the Tamelang tradition) are strongly internalized. This study concludes that the integration between the theological values of the Qur'an and the local wisdom of Masohi Custom has successfully created social cohesion and serves as an adaptive model of religious moderation in a multicultural region.